Building the right employee value proposition to retain millennial talents: A case study at a national bank in Indonesia - Intani, Agustina Lolita; Febrianto, Ari; Saragih, Eva Hotnaidah (Journal of Asian Business Strategy, 2024)
Bank ABC are dominated by the millennial generation, which makes up 65% of all employees. During the 2020-2022 period, there was an increase in the number of employees who resigned, most of whom were the millennial generation and had good performance. Meanwhile, in the next 3-5 years the millennial generation is projected to occupy strategic positions. Therefore, this study aims to develop employee value proposition (EVP) development strategy in the context of millennial talent employees’ retention. The research was conducted through a survey using Pawar and Charak’s EVP Priority Model dimension guide, equipped with additional dimensions obtained from interviews with millennial employees with high potential and performance. The survey was filled by 366 millennial talent employees. The survey results were processed and analysed using the Importance Performance Analysis (IPA) method. Results related to priority EVP attributes for development (quadrant 1 IPA results) were obtained, namely: Career development, performance appraisal, workload, work-life balance, technological innovation, annual leave and performance-based remuneration. Based on the findings obtained, a model has been built which consists of three priority areas for EVP development, namely Leader’s Future Development, Design of Organization, and Remuneration for Human Capital Sustainability (abbreviated to LDR – Leadership Development Remuneration Model), with four strategic program designs consisting of: (1) performance assessments that prioritize the principle of fairness,(2) acceleration of levels digital-based career and competency development, (3) workload analysis and job design that supports the future of work, and (4) development of competitive compensation with equitable principles.